The Russian Arctic Council Chairmanship: National Security Considerations in the Shadow of Regional Cooperation - Bouffard, Troy J; Lackenbauer, P. Whitney (DEU, 2023)
From May 2021 to 2023, Russia will hold the chairmanship of the Arctic Council for the second time in the forum’s history. As chair, it will lead the collective efforts of the foremost regional deliberative body, comprised of the eight Arctic nations, six permanent participants representing Arctic Indigenous Peoples, six working groups, and thirty-nine observer states, intergovernmental organizations, and non-governmental organizations. This represents a critical opportunity for the host country to orchestrate focused attention on the importance of the Arctic through its particular lens.